1992
DOI: 10.1136/bjsm.26.4.223
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Weil's disease among canoeists.

Abstract: Although the risks of contracting Weil's disease in the UK are small, it can be a serious illness. Recently the disease has attracted public interest. This interest has prompted confusion and anxiety among recreational water user groups such as canoeists who had not previously seen themselves as being particularly at risk. In this paper, the experience of symptoms associated with Weil's disease among canoeists, their understanding and perceptions of the disease, and their compliance with preventive advice on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…In contrast, a study among Canoeists in North Wales in 1991 revealed a very high 95% of respondents who had heard of the disease (Philipp et al, 1992). This was probably because the study was either carried out among active leptospirosis cases or the subjects were exposed to intensive information because they were exposed to a good health promotion program.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, a study among Canoeists in North Wales in 1991 revealed a very high 95% of respondents who had heard of the disease (Philipp et al, 1992). This was probably because the study was either carried out among active leptospirosis cases or the subjects were exposed to intensive information because they were exposed to a good health promotion program.…”
Section: Discussionmentioning
confidence: 58%
“…This number is comparable to the proportion registered among canoeists and dairy farmers from England where 95% and 90% of study respondents, respectively, reported having heard of leptospirosis. 14,20 Furthermore, the level of knowledge about the transmission of leptospirosis was similar among participants in this study and among canoeists from England; 88% of the respondents in Salvador and 80% in England correctly identified sources of leptospirosis transmission.…”
Section: Discussionmentioning
confidence: 73%
“…[13][14][15][16] Moreover, there is no published KAP studies conducted among residents of an urban slum community focused on leptospirosis. The main objective of this study was to describe the KAP related to leptospirosis among residents of an urban slum community where a cohort study to determine risk factors for leptospirosis infection is ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Improved hygiene awareness may be beneficial in reducing an illness contracted in this way. Although governing bodies such as the British Canoe Union provide information regarding illness and disease associated with WW activities, this information is not always accessed by WW users [26]. However, the report by Philipp et al is now dated and a more recent examination of the impact of health-related information, advice and guidelines for the prevention of illness in WW activities may be beneficial.…”
Section: Discussionmentioning
confidence: 99%